ANALISIS ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDESA) SEBELUM DAN SESUDAH PENERAPAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 DI KABUPATEN JOMBANG (Survey pada desa Kedungpapar kecamatan Sumobito Periode 2012-2016) - Sumarwiyah, Ninik; Sandari, Tries Ellia (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTAfter the passing of Law No. 6 of 2014 on 15th January 2014 This is a phenomenon that is quite large. Amendment Act 6 of 2014 occurred considerable changes ranging from power to regulate their own village to changes in the budget revenue and expenditure of the village. The purpose of this study was to determine how the budget revenue and expenditure village before and after the application of the law no.6 of 2014. This study used descriptive qualitative method. Types of data sources used are primary data and secondary data. The technique of collecting data by interview and documentation. Results of the discussion in this study is the budget revenue and expenditure village before and after the application of law No. 6 of 2014 concerning the village were analyzed by law no.6 of 2014 and related government regulations and can be obtained from the difference in the format of the structure, development and a recording system used in the kedungpapar village. This conclusion shows that before and after the application of law No. 6 of 2014 on the village applied in villages there are some fundamental differences from the format structure, up to the recording system development and preparation of budget revenue and expenditure of the village. So it takes the human resources better in order to improve the quality in the budget statement of revenue and expenditure of the village and in the preparation of the budget system is required to be accountable, transparent and participatory. Keywords: Budget, Budget revenues and expenditures of the village, a law on village